The Influence of Information Technology and The Working Environment on Employee Performance: A Study Case at Yus Corp Makassar - Nurkhasi; Djabir Hamzah; Andi Reni (The Scientia Journal of Economics Issues, 2023)
This study aims to determine whether information technology and the work environment affect employee performance at Yus Corp Makassar. Data collection used primary data obtained from a questionnaire administered to a sample of 60 employees at Yus Corp Makassar. Analysis of the data used is descriptive analysis, and multiple linear regression. Sampling technique used is saturated samples. The results revealed the following findings: 1) Information technology has a positive and significant impact on employee performance. 2) The work environment does not have a positive direct effect on employee performance. 3.) There is a Simultaneous Influence of Information Technology and Work Environment on Employee Performance at Yus Corp Makassar